DEVELOPMENT OF SERVISEMAN ІS EMOTIONAL COMPETENCE IN ACTIVE SOCIAL-PSYCHOLOGICAL TRAINING GROUPS - Gulbs, O.; Kobets, A. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article is devoted to the disclosure of the peculiarities of the development of emotional competence of servicemen in groups of active social and psychological training. It is noted that the productivity of a serviceman in interaction with others is also based on the effective perception, management and control not only of their own emotions, but also the emotions of others. Therefore, the effective activity of a serviceman directly depends on his developed emotional competence. Emotional competence, as a component of professional competence, is a set of emotional and social abilities, the ability to understand their own emotions and the emotions of others, to manage the emotional sphere. All structural components of emotional competence are interconnected, and their close interdependence promotes effective interpersonal interaction. It is assumed that servicemen with a high level of emotional competence have a strong ability to understand their own emotions and the emotions of others, to manage the emotional sphere, which leads to greater adaptability and efficiency in communication. Active socio-psychological training is psychologicalpedagogical form of development of emotional competence and improvement of abilities and skills of interaction in a society carried out in the conditions of group educational and training activity. This method was used to form in participants specific emotional, communicative, cognitive and behavioral skills, in order to increase emotional competence, communicative and psychological competence, emotional intelligence. Work in groups of active socio-psychological training is aimed at positive changes in the development of emotional competence of its participants. The effectiveness of work in groups of active socio-psychological training with servicemen is high, as the age period of early and middle adulthood involves mobility, plasticity and sensitivity of the emotional and intellectual spheres of personality. The data obtained from the results of the experiment reliably confirm the effectiveness of the method of active socio-psychological training in the development of emotional competence in servicemen.